Renewable energy sources potential evaluation in Romania - Bucur, I; Axinte, P; Plescan, C; Şerban, A (IOP Publishing, 2021)
Renewable energy sources (wind energy, solar energy, energy hydropower, ocean energy, geothermal energy, biomass and biofuels) are alternatives to conventional fuels in the greenhouse gases emissions reduction process. Because of the EU legislation support, the renewable energy sources have evolved significantly in recent years and in 2009 EU set a target of 20% energy consumption comes from renewable energy sources by 2020. In 2018, the target has been set for 32% of energy consumption from renewable energy sources by 2030. There is currently a debate on the policy framework future for the period after 2030. Greenhouse gas emissions is considered a serious threat regarding climate change, with potentially disastrous effects on humanity. The use renewable energy sources (RES), together with improved energy efficiency, can contribute to the reduction of energy consumption, the reduction of greenhouse gas emissions and, consequently, to prevent dangerous climate change. The potential of biomass, solar, hydro, wind and geothermal energy is very important, especially in recent years, due to financial support mechanisms such as green certificates, which in many European countries helped this sector to developed progressively.